ENTREPRENURSING IN THE EYES OF NURSING STUDENTS: SEBUAH STUDI FENOMENOLOGI HERMENEUTIKA - Anthony Stafford Pangemanan; Grace Fresania Kaparang; Frendy Fernando Pitoy; Nova Lina Langingi (NUTRIX, 2022)
Current and predicted economic perplexities, high unemployment rate, and difficulties of obtaining and extending of licensure should open the eyes of nursing students not to sojourn in the stereotype nurses’ mindset as employees of health care institutions only, but also to look at the option of entreprenursing. This study aims to investigate how nursing students see entreprenursing concept and give meaning to it. The research design used was hermeneutic phenomenology with Heidegger's philosophical underpinning, Van Manen's thematic analysis technique and the trustworthiness of the data ascertained. The results of the thematic analysis of hermeneutics witness the results of data saturation on the response of 9 participants. Two meanings of entreprenursing emerged from nursing students’ perspective. Independent entreprenurses are "nurses who work privately (separated from conventional health institutions) in business relation as a supporting agency to meet the health needs in the community." Secondly, the sideline entreprenurses are "nurses who work as employees of health care institutions but also having sideline jobs that support the fulfillment of the health needs in the community. However, in addition to this, there are also those who stated of not knowing anything regarding this entreprenurse concept. Then, participants also mentioned entreprenurse activities such as providing complementary therapies (juices, healthy foods and massages), opening clinics, homecare, medical device stores and training. It seems that the participants have only understood the entreprenursing concept on what the practitioners are doing and have not yet on the overall concept. Recommendations to nursing teachers to provide entreprenursing experience through on-the-job-training and also the introduction of general business terminology related to entrepreneurship. Keywords: entreprenursing, nursing students Abstrak Kesulitan ekonomi yang terjadi sekarang dan diprediksi akan semakin memburuk, tingginya pengangguran, dan susahnya mendapat dan memperpanjang STR harus membuka mata para mahasiswa keperawatan untuk tidak tinggal pada stereotipe perawat sebagai pegawai institusi layanan kesehatan tetapi juga melirik opsi entreprenursing. Studi ini bertujuan untuk menginvestigasi bagaimana mahasiswa perawat melihat entreprenursing dan mengartikannya. Desain penelitian yang digunakan adalah fenomenologi hermeneutika dengan filosofi Heidegger, teknik analisa tematik Van Manen dan keabsahan data dipastikan. Hasil analisis tematik hermeneutika diambil peneliti dari hasil saturasi data pada jawaban 9 partisipan. Ditemukan dua arti entreprenursing menurut mahasiswa keperawatan. Entreprenurse Mandiri adalah “perawat-perawat yang bekerja secara pribadi (terpisah institusi kesehatan konvensional) dalam kaitan bisnis sebagai supporting agency untuk pemenuhan kebutuhan kesehatan di masyarakat.” Kemudian, yang entreprenurse sampingan yaitu “perawat yang bekerja sebagai pegawai institusi layanan kesehatan namun juga memiliki pekerjaan bisnis sampingan yang menjadi pendukung pemenuhan kebutuhan kesehatan masyarakat. Namun, selain itu ada juga yang mengatakan bahwa dia belum ada bayangan mengenai entreprenurse ini. Kemudian, partisipan juga menyebutkan kegiatan-kegiatan entreprenurse seperti pemberian terapi komplementer (jus, makanan sehat dan massage), pembukaan klinik mandiri, homecare, toko alat kesehatan dan training. Tampaknya para partisipan baru mengerti entreprenursing dari apa yang dilakukan oleh praktisinya dan belum konsep keseluruhannya. Rekomendasi kepada pengajar keperawatan untuk dapat memberikan pengalaman entreprenursing melalui on-the-job-training dan juga pengenalan terminologi bisnis umum yang berkaitan dengan kewirausahaan. Kata Kunci: entreprenursing, mahasiswa keperawatan